Acquisition of Materials and Performance of Road Construction Projects in Kenya: A Case of Nairobi County - Seboru, Msafiri Atibu; Mulwa, Angeline Sabina; Kyalo, Dorothy Ndunge; Rambo, Charles M. (European Scientific Journal, ESJ, 2016)
This study sought to establish the influence of acquisition of materials on performance of road construction projects in Kenya: A case of Nairobi County. The objective of the study was to establish the extent to which acquisition of materials influences performance of road construction projects in Kenya. This study was anchored on the theory of controlling, theory of construction management, and stakeholder theory. The paradigm used was pragmatism and the research approach used was mixed methods. Cross sectional descriptive survey and correlational research design were used. The sample size was 74 senior engineers which comprised 30 senior engineers from consulting engineering firms and 44 senior engineers from construction companies; 74 managing directors which comprised 30 managing directors from consulting engineering firms and 44 managing directors from construction companies. A five point Likert type scale questionnaire was used to collect quantitative data while interview guides were used to collect qualitative data. The statistical tools of analysis that were used for descriptive data were frequencies, percentages, arithmetic mean and standard deviation while the statistical tools that were used for inferential statistics were Pearsonâ€™s Product Moment Correlation and Linear Regression. The Fisher (F) test was used to test the hypotheses. The results indicated that with RÂ²=0.246, F(6,40)=2.173, p=0.066>0.05, H1 was rejected and it was concluded that acquisition of materials had no statistically significant influence on the performance of road construction projects. However, establishment of quantities of materials required had a statistically significant influence on the performance of road construction projects. The study recommends that organizations that deal with road construction should have appropriate policies on establishment of quantities of materials required.